Migration and Housing in Gran Buenos Aires Agglomeration: A Study on Housing Conditions Based on a Typology of Residential Areas - Mera, Gabriela (Universidad del Rosario, 2020)
In order to contribute to the academical concern about the residential insertion of migrantsin cities, the article seeks to transcend (and complement) the potential of the thematic maps to address their spatial distribution. To do this, it proposes a typology of residential areas that takes into account the (formal or informal) form of production of the residential space and the incidence of deficit housing conditions. Working from a quantitative methodological approach that takes the National Census of Population, Households and Housing 2010 as the main source of data, the aim is to study whether migrants are located in vulnerable areas such as informal urbanizations and/or areas with concentration of deficit housing conditions, as well as capture specificities of migratory groups within (and between) different types of residential area. The work focuses on the Gran Buenos Aires Agglomeration, and the universe is limited to migrants born in Bolivia, Paraguay and Peru.